2019
DOI: 10.1186/s12870-019-1914-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals candidate genes related to phosphorus starvation tolerance in sorghum

Abstract: Background Phosphorus (P) deficiency in soil is a worldwide issue and a major constraint on the production of sorghum, which is an important staple food, forage and energy crop. The depletion of P reserves and the increasing price of P fertilizer make fertilizer application impractical, especially in developing countries. Therefore, identifying sorghum accessions with low-P tolerance and understanding the underlying molecular basis for this tolerance will facilitate the breeding of P-efficient pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 109 publications
9
27
0
Order By: Relevance
“…The 17 DEGs included nine Cytochrome P450 family members, four oxidoreductase family members, two 1-aminocyclopropane-1-carboxylate oxidase family members, one Omega-6 fatty acid desaturase, and one S-norcoclaurine synthase (Table S15). The oxidoreductase activity enrichment also had reported in other plants treated by low nutrient stresses, such as in low potassium treated pear fruit [34], in low nitrogen treated wheat [35], in low phosphorus treated sorghum [36]. The networks of the DEGs in profile 1 were conducted, and the results revealed that CYP51, a member of cytochrome P450 family was the hub gene with the highest node degree 8 (Figure 6B, Tables S5 and S6).…”
Section: Discussionsupporting
confidence: 73%
“…The 17 DEGs included nine Cytochrome P450 family members, four oxidoreductase family members, two 1-aminocyclopropane-1-carboxylate oxidase family members, one Omega-6 fatty acid desaturase, and one S-norcoclaurine synthase (Table S15). The oxidoreductase activity enrichment also had reported in other plants treated by low nutrient stresses, such as in low potassium treated pear fruit [34], in low nitrogen treated wheat [35], in low phosphorus treated sorghum [36]. The networks of the DEGs in profile 1 were conducted, and the results revealed that CYP51, a member of cytochrome P450 family was the hub gene with the highest node degree 8 (Figure 6B, Tables S5 and S6).…”
Section: Discussionsupporting
confidence: 73%
“…Part of this optimization requires a better understanding of plant physiological adaptation mechanisms under P deficiency, in interaction with both soil microorganisms and the soil itself [8]. Phytohormone signaling of P starvation is one of the main pathways which modulates plant response…”
Section: Introductionmentioning
confidence: 99%
“…Research about mineral nutrition has mainly been focused on plant responses to single nutrient deficiency. Previous studies showed that in many plants species, such as rice, Arabidopsis, maize, wheat, and sorghum, plants generate adaptive responses at morphological, physiological, biochemical, and molecular levels under NPK deficiency conditions (Wang et al 2000;Wu et al 2003;Armengaud et al 2004;Scheible et al 2004;Calderon-Vazquez et al 2011;Ma et al 2012;Curci et al 2017;Sun et al 2018;Sheflin et al 2019;Zhang et al 2019). Nitrogen deficiency results in chlorosis, growth retardation and elongated roots.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic phosphate (Pi) deficiency leads to reduced plant growth, promoted root elongation in rice and sorghum, and suppressed primary root growth in Arabidopsis, anthocyanin accumulation, phosphatase secretion, and increased lipid-related metabolism, which enhance Pi acquisition, utilization, and substitution. Pi deficiency also results in higher accumulation of some metal elements, such as aluminum (Al), iron (Fe), zinc (Zn) and calcium (Ca), as well as a decline in N and K (Misson et al 2005;Li et al 2010;Gemenet et al 2016;Zhang et al 2019). Potassium plays important role in plant physiological processes, such as in stomata aperture modulation, enzyme activation, osmoregulation, and protein and starch synthesis (Ashley et al 2006;Cochrane and Cochrane 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation